The Effect of Mindful Learning on Students’ Writing Competency - Julio Saputra, Made; Piscayanti, Kadek Sonia; Agustini, Dewa Ayu Eka (JPI (Jurnal Pendidikan Indonesia), 2020)
In developing students’ writing competency, teacher’s strategy and engagement in writing process is very crucial. The strategy of teaching writing should not only focus on language aspects but also should help the students in developing their critical thinking and problem solving skill. The current study investigated the effect of midful learning on students’ writing comptency. This study was an experiment study with posttest only control group design. 71 EFL students were involved in this study. In collecting the data,this study used writing competency test and rubric for assessing. The collected data were analzyed using descriptive and inferential statistics. The result of descprtive statistics showed that the mean score of writing competency of experiment group (82.25)  was higher than the control group (78.67). A significant mean difference is identified from the result of t test (Sig. .005.) The result of effect size test showed a medium effec (.68) t. Thus, it can be concluded that mindful learning significantly affects students’ writing competency. Discussions and suggestions are further presented.